Purification of thonningianins A and B and four further derivatives from Thonningia sanguinea by one‐ and two‐dimensional centrifugal partition chromatography. Issue 2 (11th November 2019) - Pompermaier, Luca; Schwaiger, Stefan; Mawunu, Monizi; Lautenschlaeger, Thea; Stuppner, Hermann; Faure, Karine
Abstract: Thonningia sanguinea is a parasitic herb widely used in traditional African medicine. Dihydrochalcone glucosides (unsubstituted, substituted with hexahydroxydiphenoyl or galloyl moieties) are the main constituents in the subaerial parts of this plant. In the present study, purification of the six major compounds from a methanol extract of the plant's subaerial parts was achieved by centrifugal partition chromatography. A first dimension centrifugal partition chromatography separation with the solvent system methyl tert‐butyl ether/1, 2‐dimethoxyethane/water (1:2:1) in the ascending mode enabled the isolation of the two major bioactive compounds thonningianin A and B from 350 mg of methanol extract within only 16 min with respectable yields (25.7 and 21.1 mg), purities (87.1 and 85%), and recoveries (71.2 and 70.4%). Using a multiple heart‐cutting strategy, the remaining four major dihydrochalcone glucosides of the extract were further separated in a second dimension centrifugal partition chromatography with the solvent system ethyl acetate/1, 2‐dimethoxyethane/water (2:1:1) in the descending mode with high purities (88.9–98.8%).